Given differential equation is:
"(x^4D^4+6x^3D^3+9x^2D^2+3xD+1)y=(1+lnx)^2"
Let us put, "x = e^z \\implies z = ln(x), \\frac{d}{dx} = D"
"(D(D-1)(D-2)(D-3)+6D(D-1)(D-2)+9D(D-1)+3D+1 )y = (1+z)^2"
"(D^4+2D^2+1)y = (1+z)^2"
The auxiliary equation will be,
"D^4+2D^2+1 =0"
"D = -i,-i,i,i"
Then,
"y = c_1(1+z)cos(z)+c_2(1+z)sin(z)"
P.I. "\\frac{1}{D^4+2D^2+1}(1+z)^2 = \\frac{1}{D^4+2D^2+1}(1+2z+z^2)"
"= \\frac{1}{1+(D^4+2D^2)}(1+2z+z^2) = (1+(D^4+2D^2))^{-1}(1+2z+z^2)"
Expanding "(1+(D^4+2D^2))^{-1}" binomially.
"= (1-(D^4+2D^2)+\\frac{-1(-1-1)}{2!}(D^4+2D^2)^2 + .........)(1+2z+z^2)"
"= (1+2z+z^2 - 2(2)) = (z^2+2z-3)"
The solution to the equation is,
"y = c_1(1+z)cos(z)+c_2(1+z)sin(z) + (z^2+2z-3)"
"y = c_1(1+lnx)cos(lnx) + c_2 (1+lnx)sin(lnx) + (lnx)^2+3lnx - 3"
Comments
Leave a comment